Spectroscopy and Light Emitting Diodes Based System in Characterizing External Beam Therapy 3 Films for Solar Ultraviolet Measurement - Wan Insaniah Saleha Ahmad Shah (Photonic Sensors, 2019)
Abstract Gafchromic external beam therapy 3 (EBT3) film has widely been used in medical field applications. Principally, the EBT3 film’s color gradually changes from light green to darker color under incremental exposures by ionizing or even non-ionizing ultraviolet (UV) radiation. Peak absorbance of the EBT3 film can be used to predict absorbed doses by the film. However, until today, related researches still rely on spectrometers for color analysis of EBT3 films. Hence, this paper presents a comparative analysis between results produced by the spectrometer and a much simpler light-emitting diode-photodiode based system in profiling the color changes of EBT3 films after exposure by solar UV radiation. This work has been conducted on a set of 50 EBT3 samples with incremental solar UV exposure (doses). The wavelength in the red region has the best sensitivity in profiling the color changes of EBT3 films for low solar UV exposure measurement. This study foresees the ability of blue wavelength to profile films with a large range of solar UV exposure. The LED (light emitting diode)-based optical system has produced comparable measurement accuracies to the spectrometer and thus, with a potential for replacing the need for a multipurpose spectroscopy system for simple measurement of light attenuation.